The Impact of Talkpal.AI on English Speaking Proficiency: An Academic Inquiry - Efendi Hidayatullah (Yayasan Insan Mulia Bima, 2024)
This study aims to investigate the impact of using Talkpal.AI in improving the English-speaking ability of university students. The research problem is to what extent Talkpal.AI can enhance fluency and intelligibility in English speaking. The research methodology used was quantitative research with an experimental approach where the experimental group used Talkpal.AI while the control group did not use the application. The research participants were university students with varying levels of English proficiency. Data was collected through an initial test to assess the level of English speaking ability before intervention with Talkpal.AI and a final test after a certain period of using the application. Then, an independent t-test was conducted with significant results. The findings of this study show that students have not widely used Talkpal.AI because they do not know the Talkpal.AI tool and are not facilitated by the institution. Participants in the experimental group showed considerably improved speaking fluency and clarity compared to the control group. In addition, survey results showed that participants had a positive perception of using Talkpal.AI to support English learning. This study confirms that Talkpal.AI positively impacts improving English speaking in a university setting. The implications of this research highlight the potential of Talkpal.AI as an effective tool in supporting English language learning in higher education institutions, as well as suggesting further integration of this type of technology in the English language teaching curriculum. Hopefully, this research provide valuable insights into the effectiveness of using Talkpal.AI in improving English speaking skills among university students. The results of this study can provide helpful information for developing more effective English learning strategies in the academic environment.